2015
DOI: 10.11604/pamj.2015.20.363.6629
|View full text |Cite
|
Sign up to set email alerts
|

Intérêts de l’examen du fond d’œil en pratique de ville: bilan de 438 cas

Abstract: L'examen du fond d’œil fait partie du bilan de nombreuses maladies générales en dehors de l'ophtalmologie. L'objectif de notre travail était d’étudier les aspects cliniques et épidémiologiques des patients adressés pour un fond d’œil afin de montrer l'intérêtde cet examen. Il s'est agi d'une étude rétrospective descriptive des examens du fond d’œil durant la période de janvier 2011 à décembre 2013 dans un cabinet d'ophtalmologie d'une polyclinique à Bobo Dioulasso. Au cours de la période étudiée, 5942 consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
3
Order By: Relevance
“…In our study the fundus examination accounted for 6.84%, which is lower than the Diallo et al In Burkina in 2015 which was 7.37% [7]. This could be explained by the fact that our study was conducted in a hospital setting.…”
Section: Epidemiological Aspectscontrasting
confidence: 76%
See 2 more Smart Citations
“…In our study the fundus examination accounted for 6.84%, which is lower than the Diallo et al In Burkina in 2015 which was 7.37% [7]. This could be explained by the fact that our study was conducted in a hospital setting.…”
Section: Epidemiological Aspectscontrasting
confidence: 76%
“…This could be explained that hospitalized patients would have unbalanced diabetes and poorly monitored diabetes. Diallo et al Burkina Faso found a lower rate of 25.92% [7]. Non-proliferative retinopathy was 30.26% in our study; however, the same author had found 24.53% of non-proliferative diabetic retinopathy.…”
Section: Clinical Aspects  Hypertensioncontrasting
confidence: 68%
See 1 more Smart Citation